Mothering Here and Mothering There: International Migration and Postbirth Mental Health - Stephanie S. Bouris; Lisa A. Merry; Amy Kebe; Anita J. Gagnon (Obstetrics and Gynecology International)
Over 125,000 women immigrate to Canada yearly—most in their childbearing years and many having given birth before immigrating. We sought to (1) examine the background characteristics and mental health profile of women separated from their children due to migration and subsequently giving birth in Canada (“dual-country (DC) mothers”) and (2) contrast these with those of “non-dual-country” migrant mothers. Of 514 multiparous migrant women giving birth, one-fifth (18%) reported being separated from their children due to migration. Over one-third of DC mothers were living in poverty (36.0% versus 18.6%, P=0.001), and one in seven was experiencing household food insecurity (16.3% versus 7.6%, P=0.01). Over one-third had no partner (40.2% versus 11.4%, P=0.00), and nearly one-quarter reported no available support (23.1% versus 12.2%, P=0.007). Over three-quarters were asylum seekers or refugees (83.7% versus 51%, P=0.00). More DC than non-DC mothers had symptoms of postpartum depression (28.3% versus 18.6%, P=0.04), symptoms of clinical depression (23.1% versus 13.5%, P=0.02), and anxiety related to trauma (16.5% versus 9.4%, P=0.04). Results suggest that identifying DC mothers is a rapid approach to enable clinicians to target a subgroup of women needing special attention.